CRISPR-enabled sensors for rapid monitoring of environmental contaminants - Wang, Yiting; Pan, Yuwei; Han, Wenchao; Spatola Rossi, Carla; Hui, Qingxin; Guo, Ying; Owoseni, Mojisola Christiana; McAdam, Ewan; Yong, Yang-Chun; Wang, Baojun; Yang, Zhugen (Elsevier, 2025)
There is increasing attention on the impacts of contaminants on environmental and human health. To better understand the potential threat to ecosystems and human health, biosensing has played an important role in monitoring contaminants and biomarkers. In the past decade, the integration of CRISPR-Cas systems with technologies like microfluidic devices and isothermal amplification methods has paved the way for developing advanced sensors for environmental surveillance. Here we discuss the recent progress of various CRISPR-Cas systems to develop new biosensing devices, ranging from the fundamental mechanisms to their practical applications. We present a comprehensive and critical overview on the current state-of-the-art of CRISPR-Cas-based sensing platforms, including for both nucleic acid and non-nucleic acid contaminants, as well as portable engineered systems for on-site detection. We also provide the prospects of CRISPR-Cas systems for next-generation environmental surveillance, together with emerging technologies such as data science and artificial intelligence.
Keywords: CRISPR-Cas; Portable sensors; Water contaminants; Environmental monitoring; 3401 Analytical Chemistry; 34 Chemical Sciences; Biotechnology; Bioengineering; 3 Good Health and Well Being